Monogenic autoinflammatory diseases: Cytokinopathies. Issue 2 (August 2015) - Moghaddas, Fiona; Masters, Seth L.
Abstract Rapid advances in genetics are providing unprecedented insight into functions of the innate immune system with identification of the mutations that cause monogenic autoinflammatory disease. Cytokine antagonism is profoundly effective in a subset of these conditions, particularly those associated with increased interleukin-1 (IL-1) activity, the inflammasomopathies. These include syndromes where the production of IL-1 is increased by mutation of innate immune sensors such as NLRP3, upstream signalling molecules such as PSTPIP1 and receptors or downstream signalling molecules, such as IL-1Ra. Another example of this is interferon (IFN) and the interferonopathies, with mutations in the sensors STING and MDA5, the upstream signalling regulator AP1S3, and a downstream inhibitor of IFN signalling, ISG15. We propose that this can be extended to cytokines such as IL-36, with mutations in IL-36Ra, and IL-10, with mutations in IL-10RA and IL-10RB, however mutations in sensors or upstream signalling molecules are yet to be described in these instances. Additionally, autoinflammatory diseases can be caused by multiple cytokines, for example with the activation of NF-κB/Rel, for which we propose the term Relopathies. This nosology is limited in that some cytokine pathways may be degenerate in their generation or execution, however provides insight into likely autoinflammatory disease candidates and the cytokines with which newly identified mutations may be associated, and therefore targeted.